Collaborative teaching work and pedagogical management in regular basic education institutions in the El Agustino district, Lima - Cruzado Pacheco, Brisa Eden (2024)
The research aimed to determine the correlation between collaborative teaching work and pedagogical management in educational institutions in El Agustino district, Lima. The analysis of the variables was conducted under a quantitative, non-experimental approach, with a cross-sectional correlational design. The study involved 143 teachers working in public educational institutions in the district at secondary (45.45%), primary (20.28%), and initial (34.27%) levels. Data collection was carried out using the survey technique, and three questionnaires were developed: sociodemographic, on collaborative teaching work with a reliability of (>0.91), and on pedagogical management with a reliability of (>0.80), each validated by expert judgment. The analysis of the collected data confirms the general hypothesis, finding that there is a correlation between collaborative teaching work and pedagogical management with a correlation coefficient (p) of 0.6892, a p-value < 0.0001, and a 95% confidence interval between 0.5700 and 0.7864. Specific hypotheses were also confirmed.